Evaluation of oil transesterification in a packed-bed reactor containing lipase immobilized in starch–alginate jet cutting beads - Almeida, Francisco Lucas Chaves [UNESP]; Sampaio, Klicia Araujo; Prata, Ana Silvia; Forte, Marcus Bruno Soares [UNESP] (Wiley, 2024)
There has been a growing interest in ecofriendly enzymatic processes. However, enzyme solubility limits the application of many biocatalysts in continuous systems, requiring the development of cost-effective strategies for enzyme immobilization. Based on this premise, this study investigated the application of lipase immobilized in starch–alginate beads for oil transesterification in a tubular reactor. An economical derivative was produced by immobilizing Eversa Transform 2.0 in 50:50 (w/w) starch–alginate beads using the jet-cutting technique. The biocatalyst had a particle size of about 500 μm and activity of 138.67 ± 18.53 U g−1. X-ray photoelectron spectroscopy showed nitrogen content ranging from 6.38% to 7.29%, with uniform distribution of lipase throughout the beads. Nitrogen isotherms were characteristic of mesoporous materials, with an average pore diameter of 48.09 Å and low surface area (0.69 m2 g−1). A face-centered central composite design was used to study soybean oil transesterification. In the best four runs, the process achieved a mean triglyceride conversion of 45%. High ester productivity levels (2.05 × 10−2% ester g−1 biocatalyst min−1 or 1.5 × 10−4% ester U−1 min−1) were obtained. Biocatalyst reuse led to a twofold increase in ester concentration (14.57% vs 7.7%). These findings confirm the successful development of a low-cost biocatalyst suitable for use in continuous reactions.
Keywords: biodiesel; continuous process; Eversa transform 2.0; jet cutting; lipase immobilization